2023
DOI: 10.1088/1361-6595/acc274
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of production of keV Sn+ ions in the H2 buffer gas surrounding an Sn-plasma EUV source

Abstract: Charge-state-resolved kinetic energy spectra of Sn ions ejected from a laser-produced plasma (LPP) of Sn have been measured at different densities of the H2 buffer gas surrounding a micro-droplet LPP. In the absence of H2, energetic keV Sn ions with charge states ranging from 4+ to 8+ are measured. For the H2 densities used in the experiments no appreciable stopping or energy loss of the ions is observed. However, electron capture by Sn ions from H2 results in a rapid shift towards lower charge states. At the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…is endothermic with an energy difference of 1.3 eV for the Franck-Condon ionization of H 2 at its equilibrium distance, it has been believed that the consecutive charge state lowering basically stops at 2+. However, in a recent study [11], we have shown that the successive capture reactions do lead to the formation of Sn + ions. The work of Rai et al [11] explains the high production of Sn + as a consequence of the preceding single-capture reaction between Sn 3+ and H 2 , which was shown [15] to mainly produce long-lived metastable Sn 2+ (5s5p…”
Section: Introductionmentioning
confidence: 79%
See 3 more Smart Citations
“…is endothermic with an energy difference of 1.3 eV for the Franck-Condon ionization of H 2 at its equilibrium distance, it has been believed that the consecutive charge state lowering basically stops at 2+. However, in a recent study [11], we have shown that the successive capture reactions do lead to the formation of Sn + ions. The work of Rai et al [11] explains the high production of Sn + as a consequence of the preceding single-capture reaction between Sn 3+ and H 2 , which was shown [15] to mainly produce long-lived metastable Sn 2+ (5s5p…”
Section: Introductionmentioning
confidence: 79%
“…However, in a recent study [11], we have shown that the successive capture reactions do lead to the formation of Sn + ions. The work of Rai et al [11] explains the high production of Sn + as a consequence of the preceding single-capture reaction between Sn 3+ and H 2 , which was shown [15] to mainly produce long-lived metastable Sn 2+ (5s5p…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…2 where the difference in ionization levels is only 0.44 eV. However, work by Rai et al [16,33] has shown evidence of single ionized tin coming from a laser-produced-plasma. These singly ionized tin particles only appear after hydrogen gas is introduced and higher charged tin ions are charge exchanged down.…”
Section: Introductionmentioning
confidence: 98%